Interaction of engineered nanomaterials with hydrophobic organic pollutants. (6th June 2016) - Sahle-Demessie, E; Han, Changseok; Zhao, Amy; Hahn, Bill; Grecsek, Heidi
Abstract: As nanomaterials become an increasing part of everyday consumer products, it is imperative to monitor their potential release during production, use and disposal, and to assess their impact on the health of humans and the ecosystem. This necessitates research to better understand how the properties of engineered nanomaterials (ENMs) lead to their accumulation and redistribution in the environment, and to assess whether they could become novel pollutants or if they can affect the mobility and bioavailability of other toxins. This study focuses on understanding the influence of nanostructured-TiO2 and the interaction of multi-walled carbon nanotubes with organic pollutants in water. We studied the adsorption and water phase dispersion of model pollutants with relatively small water solubility (i.e., two- and three-ring polyaromatic hydrocarbons and insecticides) with respect to ENMs. The sorption of pollutants was measured based on water phase analysis, and by separating suspended particles from the water phase and analyzing dried samples using integrated thermal–chromatographic–mass spectroscopic (TGA/GC/MS) techniques. Solid phase analysis using a combination of TGA/GC/MS is a novel technique that can provide real-time quantitative analysis and which helps to understand the interaction of hydrophobic organic pollutants and ENMs. The adsorption of these contaminants to nanomaterials increased the concentration of the contaminants in the aqueous phase as compared to the 'real' partitioning due to the octanol–water partitioning. The study showed that ENMs can significantly influence the adsorption and dispersion of hydrophobic/low water soluble contaminants. The type of ENM, the exposure to light, and the water pH have a significant influence on the partitioning of pollutants.